The Everyday Practices of Dialysis and Kidney Transplant in Egypt - Abu El Ela, Abdelrazek (AUC Knowledge Fountain, 2024)
This thesis is an autoethnography of the lived experiences of kidney disease and transplantation, through the lens of everyday life. I combine my own autoethnographic accounts of my experiences going through kidney disease, failure, dialysis, and eventually organ transplantation, with participant observation of other kidney patients and transplant recipients, as well as ethnographic research with a kidney donor. In doing so, and by employing an actor-network theoretical framework, this thesis moves away from seeing the kidney as simply a diseased organ or an object to medical intervention. Instead, it aims to unravel the multiplicity, contradictions and myriad of layers that comprise what we label kidney transplant. I connect my autoethnographic account to the cultural, the social, and the political fields within which kidney disease operates in Egypt and examine the way bodies carrying diseased organs are entangled with overindebted subjects, causing new possibilities to emerge – possibilities that sustain life. I place the social at the center of the analysis, and delve into questions of time, space, bodies, and the relationships between humans and non-humans. I move through these entanglements with a sensibility towards the messiness of the different fields through which diseased bodies operate, and with the aim of understanding how we can account for the messy worlds of diseased subjectivities.